Meccanica - Fanti, Marcello (Milano University Press, 2021)
Newtonian Mechanics is one of the first subjects a university student encounters in a scientific degree: it is important to address it with rigour and depth, but also to learn to recognise it, in all its manifestations, in the world around us. For this reason, all the topics covered are accompanied by numerous examples taken from everyday situations, or from astronomy or particle physics. Extensive treatment is given to fictitious forces, rigid body dynamics, and universal gravitation - one of the most fascinating achievements of this discipline. An introduction to Special Relativity completes the work. Within the text, several chapters are devoted to the introduction of specific mathematical tools. About 200 figures complete the exposition.